High plasma organochlorine pesticide levels are related to increased biological age as calculated by DNA methylation analysis - P. Monica Lind; Samira Salihovic; Lars Lind (Environment International, 2018)
Background: Organochlorine pesticides (OCPs) have been shown in the experimental setting to alter DNA methylation. Since DNA methylation changes during the life-span, formulas have been presented to calculate “DNA methylation age” as a measure of biological age. Objectives: We aimed to investigate if circulating levels of three OCPs were related to increased DNA methylation age Methods: 71CpG DNA methylation age (Hannum formula) was calculated based on data from the Illumina 450 k Bead Methylation chip in 1000 subjects in the Prospective Study of the Vasculature in Uppsala Seniors (PIVUS) study (50% women, all aged 70 years at the examination). The difference between DNA methylation age and chronological age was calculated (DiffAge). 2,2-bis (4-chlorophenyl)-1,1-dichloroethene (p,p′-DDE), hexachlorobenzene (HCB), and transnonachlor (TNC) levels were measured in plasma by high-resolution gas chromatography coupled mass spectrometry (HRGC-HRMS). Results: Increased p,p′-DDE and TNC, but not HCB, levels were related to increased DiffAge both in sex and BMI-adjusted models, as well as in multiple adjusted models (sex, education level, exercise habits, smoking, energy and alcohol consumption and BMI) (p = 0.0051 and p = 0.011, respectively). No significant interactions between the OCPs and sex or BMI regarding DiffAge were found. Conclusion: In this cross-sectional study, increased levels of two out of three OCPs were related to increased DNA methylation age, further suggesting negative health effects in humans of these widespread environmental contaminants. Keywords: Methylation, Biological age, p,p′-DDE, Transnonachlor, Epidemiology, Organochlorine pesticides (OCPs)